Chest response assessment of post-mortem swine under blast loadings. (8th December 2017) - Boutillier, Johanna; De Mezzo, Sébastien; Deck, Caroline; Magnan, Pascal; Naz, Pierre; Willinger, Rémy
Abstract: To better protect soldiers from blast threat, that principally affect air-filled organs such a lung, it is necessary to develop an adapted injury criterion and, prior to this, to evaluate the response of a biological model against that threat. The objective of this study is to provide some robust data to quantify the chest response of post-mortem swine under blast loadings. 7 post-mortem swine (54.5 ± 2.6 kg), placed side-on to the threat and against the ground, were exposed to 5 shock-waves of increasing intensities. Their thorax were instrumented with a piezo-resistive pressure sensor, an accelerometer directly exposed to the shock-wave and a target was mounted on the latter in order to track the chest wall displacement. For incident impulses ranging from 47 kPa ms ± 2% to 173 kPa ms ± 6%, the measured maximum of linear chest wall acceleration (Γmax) goes from 5800 m/s 2 ± 16% to 41, 000 m/s 2 ± 8%, with a duration of 0.8 ms. Chest wall displacements ranging from 5 mm ± 20% to 20 mm ± 15%, with a duration of 9 ms, are reached. These reproducible data were used to find simple relations (linear, 2nd and 3rd order polynomials) between the kinematic parameters (plus the viscous criterion) and the incident and reflected impulses. Correlating the new reproducible data with the prediction from the Bowen curves showed a lung injury threshold in terms of Γmax similar to that of Cooper (10, 000 m/s 2 ). However, the limits defined for the viscous criterion in the automobile field and for non-lethal weapons seems not adapted for the blast threat.